Pediatric Hypertension Specialists' Perspectives About Adolescent Hypertension Management: Implications for Primary Care Providers. (June 2015) - Yoon, Esther; McCool, Brigitte; Filipp, Stephanie; Rocchini, Albert; Kershaw, David; Clark, Sarah
Background . The current specialty-centric hypertension paradigm is unsustainable given the high prevalence of primary hypertension in adolescents. Objective . To describe specialists' perspectives on referral and comanagement for adolescents with hypertension. Methods . Cross-sectional mailed survey of a national sample of 397 pediatric cardiologists and 389 pediatric nephrologists, conducted January to May 2014. Results . Response rate was 61%. Both specialties agreed that primary care providers can make the hypertension diagnosis, try lifestyle changes, and comanage monitoring of patient blood pressure control and medication side effects, but they felt antihypertensive medication use should mainly occur in the specialty setting. Conclusions . Our study suggests specialist support for changing the hypertension paradigm to encourage primary care providers, in collaboration with specialists, to diagnose hypertension, initiate lifestyle changes, and monitor progress and side effects. Future work should focus on supporting primary care physician comanagement of adolescents with hypertension.